Konsep dan Prinsip Perencanaan Pendidikan Islam Dalam Perspektif Al-Quran dan Hadis - Roifah, Zahrotur; Rizqiya, Nila Nabilatul (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2026)
Planning in Islam emphasizes the systematic, orderly, efficient, and responsible implementation of every activity as part of the mandate of human stewardship on earth. In the context of education, planning has a strategic role in shaping students who are faithful, knowledgeable, and noble in character, as well as capable of contributing constructively to social life. This study aims to examine and formulate the concepts and principles of Islamic educational planning based on the perspectives of the Qur'an and Hadith. The study uses a library research approach by examining verses from the Qur'an, the Prophet's hadith, and academic literature relevant to Islamic educational planning. The results of the study show that Islamic education planning is holistic, integrative, and future-oriented, combining spiritual, moral, intellectual, and social dimensions in a balanced manner. The main principles found include holistic balance, gradual planning (tadarruj) and priority setting, visionary orientation, moral responsibility (amanah), benefit, as well as deliberation and collectivity. In addition, Islamic education planning emphasizes the importance of adapting to the dynamics of the times, optimal utilization of resources, and wise management of time and potential. This study concludes that Islamic education planning must integrate human efforts with faith in Allah SWT so that the goals of education that balance worldly and hereafter life can be achieved and produce a superior generation that is ready to face contemporary challenges.